2014
DOI: 10.1111/biom.12246
|View full text |Cite
|
Sign up to set email alerts
|

Computational Aspects of N-Mixture Models

Abstract: The N-mixture model is widely used to estimate the abundance of a population in the presence of unknown detection probability from only a set of counts subject to spatial and temporal replication (Royle, 2004, Biometrics 60, 105–115). We explain and exploit the equivalence of N-mixture and multivariate Poisson and negative-binomial models, which provides powerful new approaches for fitting these models. We show that particularly when detection probability and the number of sampling occasions are small, infinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
119
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(125 citation statements)
references
References 29 publications
6
119
0
Order By: Relevance
“…Model estimates based on simulated data recovered true parameters well. This was not surprising, as previous simulation studies have shown that N ‐mixture models usually perform well for estimating abundance and detection probability for a variety of conditions with varying level of detection probability, few replicate temporal counts, and few sites (Couturier, Cheylan, Bertolero, Astruc, & Besnard, ; Dennis, Morgan, & Ridout, ; Hunt, Weckerly, & Ott, ; Kéry, Royle, & Schmid, ; McCaffery, Nowak, & Lukacs, ; Yamaura, ). The novel application in our simulation was the use of the intersection of two overlapping spatial sites as temporal replication.…”
Section: Discussionmentioning
confidence: 73%
“…Model estimates based on simulated data recovered true parameters well. This was not surprising, as previous simulation studies have shown that N ‐mixture models usually perform well for estimating abundance and detection probability for a variety of conditions with varying level of detection probability, few replicate temporal counts, and few sites (Couturier, Cheylan, Bertolero, Astruc, & Besnard, ; Dennis, Morgan, & Ridout, ; Hunt, Weckerly, & Ott, ; Kéry, Royle, & Schmid, ; McCaffery, Nowak, & Lukacs, ; Yamaura, ). The novel application in our simulation was the use of the intersection of two overlapping spatial sites as temporal replication.…”
Section: Discussionmentioning
confidence: 73%
“…Dennis et al. () show that the Binmix model with Poisson mixture can sometimes yield estimates of abundance and detection probability ( p ) that are infinite and zero, respectively. They found this especially for small abundance, detection probability and number of repeat visits.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, stability of the estimates for increasing K can be used as a criterion for parameter identifiability (Dennis et al. , Haines ). Barker et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have compared estimates between N-mixture and other models that accommodate imperfect detection using field data Hunt et al 2012;Couturier et al 2013). In addition, some simulation studies related to their performance have also been conducted (Ke´ry 2008;McIntyre et al 2012;Yamaura 2013;Dennis et al 2015). However, estimation performance of community N-mixture abundance models has not been examined to date.…”
Section: Introductionmentioning
confidence: 99%